A New Method Based on the RKHSM for Solving Systems of Nonlinear IDDEs with Proportional Delays. (23rd April 2013) - He, Changbo; Lv, Xueqin; Niu, Jing
Abstract : An efficient computational method is given in order to solve the systems of nonlinear infinite-delay-differential equations (IDDEs) with proportional delays. Representation of the solution and an iterative method are established in the reproducing kernel space. Some examples are displayed to demonstrate the computation efficiency of the method.